The Plenus Cold Event Record in the Abyssal DSDP Site 367 (Cape Verde, Central Atlantic): Environmental Perturbations and Impacts on the Nitrogen Cycle - Riquier, Laurent; Cadeau, Pierre; Danzelle, Julien; Baudin, François; Pucéat, Emmanuelle; Thomazo, Christophe (Frontiers in Earth Science, 2021)
The Oceanic Anoxic Event 2, at the Cenomanian-Turonian boundary (∼93.9 Ma), was an episode of widespread burial of organic matter in marine sediments, underlined by a positive carbon-isotope (δ13C) excursion observed worldwide. Within this episode of O2-depleted conditions, a short interval of cooling, termed as the Plenus Cold Event, has been recorded in many sites and sections in the northern hemisphere (Tethyan domain, Western Interior Seaway, proto-North Atlantic Ocean). But, its record and its impact on the biogeochemical cycles of carbon and nitrogen in the southern part of Central Atlantic Ocean has not been explored yet. Here, we present a detailed geochemical study of the Deep Sea Drilling Project site 367 (Cape Verde) based on a compilation of previous and new data of carbon and nitrogen isotope signals as well as trace element concentrations. The aim of this study is to better constrain the evolution of oxygenation in the water column and the associated changes in nitrogen cycle before and during the Oceanic Anoxic Event 2 in order to understand the paleoceanographic and environmental consequences of the Plenus Cold Event at one of the deepest site of the Central Atlantic Ocean. Our new dataset improves the resolution of the δ13C curve for this site, and we propose a new chemo-stratigraphic frame of the carbon excursion allowing for a better identification of the short-term negative carbon isotope excursion associated to the Plenus Cold Event. The detailed evolution of redox-sensitive proxies (Mo, U, V, Fe, Cu, Ni enrichments and Corg/Ptotal) and isotopic signals (δ13Corg and δ15Ntotal) evidence that this deep site was impacted by this cooling event. While anoxic conditions prevailed in bottom waters before and during the onset of the Oceanic Anoxic Event 2 characterized by euxinic NH4+-rich water column, this cooling event was accompanied by reoxygenation of the water column, which had affected the behavior of the redox-sensitive elements and caused changes in nitrogen biogeochemical cycling.